Synthesis of New Asymmetrical Pyromellitdiimide and Their Amic Acids Containing Heterocyclic Unit - Tomma, Jumbad H.; AL-Aliawi, Kadhim M. Lazim; Ali, Imad T. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This work involves the synthesis and characterization of  asymmetrical  pyromellitdiimide derivatives [VII]a-f  by four sequences steps reaction . One mole of pyromellitic dianhydride was reacted with one mole of various primary aromatic amines [2aminothiazole , 2-aminobenzothiazole , 5-(4-amino phenyl)-1,3,4-oxadiazole-2-thiol , 4-nitro aniline , 4-chloro aniline , 4-toludine] in excess of dry acetone to produce six compounds (Nsubstituted-pyromellitamic monoacid) [IV]a-f . These new compounds [IV]a-f  were converted to the  corresponding N- substituted- pyromellitmonoimide [V]a-f  when heating then at (8090) 0C in sodium acetate-acetic anhydride system .The compounds [V]d-f were allowed to react with one mole of another primary amines (containing benzothiazole or 1,3,4-oxadiazole unit) in dry acetone to give new derivatives of amic acid [VI]a-f  followed by intramolecular cyclization reaction of these compounds in sodium acetate-acetic anhydride system to yield the desired asymmetrical pyromellitdiimide derivatives [VII]a-f, the above reactions can be summarized in Scheme 1. Structures of the synthesized compounds have been ascertained by their melting points , C.H.N analysis , UV-Vis, FTIR and 1HNMR spectroscopy.